UPAYA PENINGKATAN KUALITAS MENGAJAR GURU DAPAT MENINGKATKAN JUMLAH SISWA DI MADRASAH IBTIDAIYAH SWASTA AL MUTTAQIN - Mahlil Mahlil (Universitas Negeri Medan, 2022)
Abstract: Efforts to Improve Teacher Teaching Quality Can Increase the Number of Students at Al Muttaqin Private Islamic Madrasah. Planned and continuous guidance in academic supervision through group supervision techniques is considered more effective because any problems found can be immediately found together and the time can be adjusted to the abilities of each teacher, and is expected to improve the quality of teachers. Qualified teachers will at least increase students' enthusiasm for learning, both at school and at home. This is a motivation for the surrounding community to send their children to the school, even though the situation is in a state of the covid 19 pandemic. The Al Muttaqin Tanjung Putus Foundation which was founded by Mr. Nurman, S.Pd. One of them is Madrasah Ibtidaiyah Swasta (MIS) which was established in 2007 until now, which is located at Karang Sari hamlet, Tanjung Putus village, Padang Tualang sub-district, Langkat district, North Sumatra, the area is far from urban areas, has students who continue to increase every year. Starting from grades one to six, in 2017/2018 it has 303 students, in 2018/2019 it has 305 students, in 2019/2020 it has 307 students, in 2020/2021 it has 316 students. people, in 2021/2022 it has 319 students, in 2022/2023 it has 328 students. The number of MIS Al Muttaqin students continues to grow due to efforts to improve the quality of teachers, one of which is through continuous coaching.